2022
DOI: 10.21608/edj.2022.140174.2118
|View full text |Cite
|
Sign up to set email alerts
|

Essential Oil Modification of Glass Ionomer Cement: Antibacterial Activity and Compressive Strength

Abstract: Objective: The current study was conducted to investigate the effect of essential oil (EO) modification of glass ionomer cement (GIC) on antibacterial activity and compressive strength.Methods: A total of 100 specimens were prepared; 50 specimens for the antibacterial activity test (3 mm x 2 mm) and 50 specimens for the compressive strength test (4 mm x 6 mm). Specimens were divided into five groups (n=10) according to the type of the essential oil used in modification of GIC; Group 1: unmodified glass ionomer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 32 publications
(40 reference statements)
0
0
0
Order By: Relevance
“…Flavonoids and terpenoids present in lemongrass extract could be the reason behind inhibiting bacterial growth, as terpenoids possess strong antibacterial effects [ 27 ]. Elkorashy reported that lemongrass essential oil modification of GIC effectively improved its antibacterial properties, which is consistent with our findings [ 28 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Flavonoids and terpenoids present in lemongrass extract could be the reason behind inhibiting bacterial growth, as terpenoids possess strong antibacterial effects [ 27 ]. Elkorashy reported that lemongrass essential oil modification of GIC effectively improved its antibacterial properties, which is consistent with our findings [ 28 ].…”
Section: Discussionsupporting
confidence: 93%
“…This finding aligns with a previous study [ 29 ], which indicated that the inclusion of antibacterial materials at specified concentrations did not impact the compressive strength properties of GIC, consistent with our results. Another study by Elkorashy mentioned lower compressive strength values when lemongrass essential oil was combined with GIC [ 28 ]. This effect could be attributed to the essential oil’s presence within GIC, which may hinder COOH group interactions within the glass ionomer matrix, potentially slowing down the setting reaction and affecting compressive strength.…”
Section: Discussionmentioning
confidence: 99%